Assessment of Severity of Anxiety and Depression in Covid-19 Patients Admitted to Rawalpindi Medical University and Allied Hospitals Rawalpindi Pakistan - Sadia Yasir, Ghulam Fatima, Zarnain Umar, Zona Tahir, Qasim Malik, Azfar Maqsood, Sultan Muhammad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the prevalence of anxiety and depression among the COVID-19 infected patients. Study design: Descriptive cross-sectional study. Place and Duration of Study: Rawalpindi Medical University and Allied Hospitals Covid designated wards from 1st April 2019 and 30th June 2020 Methodology: Hundred patients of either gender presented with Covid-19 infection were enrolled. Detailed demographics and complete medical examination was done after taking informed written consent. Those patients who fulfil the clinical criteria Hamilton rating scale for anxiety (HAMA) and Hamilton rating scale for depression (HRSD) were applied to assess the severity of anxiety and/or depression. Results: There were 69 (69%) males and 31 (31%) females. Eighty two (82%) patients fall in the age range of 21 to 50 years with the mean of 38 years. There is high level of anxiety as well as depression among admitted patients suffering from COVID-19. Seventy five (75%) patients suffered from depression and 72 (72%) of patients suffered from anxiety ranging from mild to severe. Conclusion: It is concluded that patients suffering from Covid-19 disease had high prevalence of depression and anxiety. Keywords: Covid 19, Anxiety and depression, Physical comorbidities